2022
DOI: 10.3389/fpsyg.2021.768748
|View full text |Cite
|
Sign up to set email alerts
|

CYP2D6 Genetic Variation and Antipsychotic-Induced Weight Gain: A Systematic Review and Meta-Analysis

Abstract: BackgroundAntipsychotic-induced weight gain is a contributing factor in the reduced life expectancy reported amongst people with psychotic disorders. CYP2D6 is a liver enzyme involved in the metabolism of many commonly used antipsychotic medications. We investigated if CYP2D6 genetic variation influenced weight or BMI among people taking antipsychotic treatment.MethodsWe conducted a systematic review and a random effects meta-analysis of publications in Pubmed, Embase, PsychInfo, and CENTRAAL that had BMI and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 90 publications
2
11
0
Order By: Relevance
“…Studies relying on large sample size underlined increased weight gain [51], prolactin levels [77], risk of EPS [71], and impaired treatment response [52] in patients deprived from at least one functional allele for CYP2D6, resulting in increased drug exposure. While the findings regarding movement abnormalities and lack of therapeutic effect concur with existing evidence [84,85], AIWG [86] and hyperprolactinemia [87] were not consistently linked with CYP2D6 impairments. However, olanzapine is mostly metabolized by CYP1A2 (and to a lesser extent by CYP2D6 and CYP3A4) [88,89], clozapine is mainly metabolized by CYP3A4 and CYP1A2 (with CYP2D6 playing a minor role) [16,90], and loxapine is primarily metabolized by CYP1A2 (then by CYP3A4 and CYP2D6) [19].…”
Section: Discussionsupporting
confidence: 81%
“…Studies relying on large sample size underlined increased weight gain [51], prolactin levels [77], risk of EPS [71], and impaired treatment response [52] in patients deprived from at least one functional allele for CYP2D6, resulting in increased drug exposure. While the findings regarding movement abnormalities and lack of therapeutic effect concur with existing evidence [84,85], AIWG [86] and hyperprolactinemia [87] were not consistently linked with CYP2D6 impairments. However, olanzapine is mostly metabolized by CYP1A2 (and to a lesser extent by CYP2D6 and CYP3A4) [88,89], clozapine is mainly metabolized by CYP3A4 and CYP1A2 (with CYP2D6 playing a minor role) [16,90], and loxapine is primarily metabolized by CYP1A2 (then by CYP3A4 and CYP2D6) [19].…”
Section: Discussionsupporting
confidence: 81%
“…For treatment response, three meta-analysis studies reported in a mixed population, Caucasians and Asians separately [ 40 , 41 , 42 ]; one meta-analysis study reported in a mixed population and Caucasians [ 31 ]; six meta-analysis studies reported in mixed populations only [ 34 , 43 , 44 , 45 , 46 , 47 ]; one meta-analysis study reported in Asians [ 48 ]. For antipsychotic-induced weight/BMI gain, two meta-analysis studies reported in a mixed population, Caucasians and Asians separately [ 49 , 50 ]; two meta-analysis studies reported in a mixed population and Asians separately [ 51 , 52 ]; three meta-analysis studies reported in mixed population only [ 35 , 53 , 54 ]; one meta-analysis study did not state the ethnicity of the population [ 32 ]. One meta-analysis study reported antipsychotic-induced metabolic syndrome in a mixed population, Caucasians and Asians separately [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…For CYP2D6 and CYP2C19 , the number inside represents the number of phenotypes of this enzyme analyzed. References: Study 1, Hwang, 2010 [ 34 ]; 2, Zhang, 2010 [ 46 ]; 3 de Matos, 2015 [ 47 ]; 4, Huang, 2016 [ 43 ]; 5, Gressier, 2016 [ 31 ]; 6, Cargnin, 2016 [ 40 ]; 7, Takekita, 2016 [ 44 ]; 8, Ma, 2019 [ 48 ]; 9, Yoshikawa, 2020 [ 45 ]; 10, Yan, 2022 [ 41 ]; 11, Liu, 2022 [ 42 ]; 12, Sicard, 2010 [ 35 ]; 13, Shen, 2014 [ 51 ]; 14, Ma, 2014 [ 49 ]; 15, Zhang, 2016 [ 32 ]; 16, Suetani, 2017 [ 53 ]; 17, Yoshida, 2020 [ 52 ]; 18, Chen, 2020 [ 50 ]; 19, Wannasuphoprasit, 2021 [ 54 ]; 20, Miura, 2016 [ 55 ]; 21, Calafato, 2020 [ 56 ]; 22, Zai, 2010a [ 59 ]; 23, Zai, 2010b [ 60 ]; 24, Miura, 2014 [ 57 ]; 25, Lv, 2016 [ 58 ]; 26, Islam, 2022 [ 61 ]; 27, Takuathung, 2019 [ 64 ]; 28, Zhang, 2019 [ 63 ]; 29, Milosavljevic, 2021 [ 62 ]. Abbreviation: Chr, chromosome; AP, antipsychotics; AIWG, antipsychotic-induced weight gain; MetS, metabolic syndrome; PRL, prolactin; TD, tardive dyskinesia; CIA, clozapine-induced agranulocytosis.…”
Section: Figurementioning
confidence: 99%
“…A recently published systematic review examining whether patients with CYP2D6 PM status on long-term antipsychotic drug treatment have an average higher body weight than patients with normal CYP2D6 metabolic capacity shows conflicting results [ 27 ]. This might be a consequence of the small number of PMs (N = 93, 4.5% of all patients), notwithstanding the large size and comprehensive nature of the review.…”
Section: Discussionmentioning
confidence: 99%